A Short Review on Vaccine Barriers in Afghanistan - Khan, Ahmad; Rahimi, Ferishta; Malak, Ulfatullah; Qazizai, Madina (Jour Med Resh and Health Sci, 2023)
In preventive medicine, vaccines are critical to decreasing the burden of vaccine-preventive diseases. In the last few decades, vaccines have decreased the mortality rate among children, and vaccine coverage has improved. On the other hand, in lower-income countries like Afghanistan, sustainable immunization is still challenging for various reasons. It is essential to investigate the potential barriers locally, such as vaccine hesitancy and other factors, to build up local evidence to formulate effective policies. However, the number of studies on vaccination is limited in lower-income countries like Afghanistan. In Afghanistan, a small number of studies have been conducted on the phenomenon of COVID-19 vaccine hesitancy, and it is not feasible to determine from conducted study results if people have the same level of hesitancy toward other vaccines, or if the present rumors and myths about the COVID-19 virus impacted people's perception of the COVID-19 vaccine. The purpose of this short review is to elaborate on the potential barriers to vaccine programs in lower-income countries like Afghanistan and suggest future studies to build up local evidence to appropriately fill in the gaps to sustain vaccine programs and prevent the burden of vaccine-preventable diseases in the country.